KEDUDUKAN HUKUM SURAT TELEGRAM KABARESKRIM KEPOLISIAN REPUBLIK INDONESIA TENTANG PENGEMBALIAN KERUGIAN KEUANGAN NEGARA MENGENYAMPINGKAN TINDAK PIDANA KORUPSI - Tampubolon, Subiarto Aprido; Harahap, Irawan; Kadaryanto, Bagio (The Juris, 2024)
The policy of returning state losses to drop criminal proceedings that have the potential to weaken law enforcement, damage legal certainty, create moral hazard, and be unfair to the wider community. Returning state losses is important, but the criminal law process against perpetrators of corruption must continue to maintain the principle of justice, ensure a deterrent effect, and maintain the integrity of law in Indonesia. The method used is normative legal research. Based on the results of the study, it is known that the legal position of the telegram from the Head of the Criminal Investigation Unit of the Republic of Indonesia Police regarding the return of state financial losses ignoring criminal acts of corruption in the perspective of legal certainty is that the return of state financial losses that ignore criminal acts of corruption should be reviewed so as not to conflict with the principle of legal certainty. Efforts to return state losses are indeed important, but they must not eliminate criminal sanctions against perpetrators of corruption. Enforcement of corruption law must be carried out firmly to provide a deterrent effect and ensure the achievement of the expected justice in the legal system. Legal certainty is an important key in maintaining the integrity of law enforcement, especially in corruption cases that harm the public interest. The legal consequences of the telegram from the Head of the Criminal Investigation Unit of the Republic of Indonesia Police regarding the return of state financial losses by ignoring corruption in the perspective of legal certainty are the legal consequences of the Telegram Letter from the Head of the Criminal Investigation Unit which regulates the return of state losses by ignoring corruption in the perspective of legal certainty, creating several serious impacts on the legal system in Indonesia. This policy weakens the principle of legal certainty, reduces the deterrent effect, and damages the integrity of the function of criminal law in the context of corruption. In order to maintain public trust and ensure substantive justice, it is important for this policy to be reviewed so that it remains in line with the basic principles of law enforcement, especially in eradicating corruption that is detrimental to the state and society.